Non traditional Innovative Warehouse Layout Types and Designs - Ayca Özceylan; Mehmet Tanyaş (Journal of Transportation and Logistics)
With the increasing variety of logistics operations, suppliers, and business models, warehouses are increasingly playing an integral role in supply chains. For this reason, warehouses must provide flexibility, accessibility, and efficient functionality more than ever before. Unfortunately, most businesses still use traditional warehouse layout models and focus on warehouse costs rather than the layout. However, if warehouse operations are more effectively performed, less energy will be consumed, leading to increased flexibility in the future. It is necessary to focus on more modern, innovative, and nontraditional warehouse layouts rather than the traditional layout models. Aisle designs that provide access to products in nontraditional innovative warehouse layouts are different from traditional warehouse aisle designs. The main motivation of the nontraditional warehouse design studies is to shorten access distances to the product to reduce the travel time in the warehouse. Aiming to present the nontraditional innovative warehouse layouts focusing on the gaps for researchers and those in the sector, this study analyzes the nontraditional innovative warehouse layouts used or suggested both in the literature and in practice, namely the Flying-V, Fishbone, Inverted-V, Chevron, Leaf, and Butterfly aisle designs, and tries to explain each one in detail with reference to the literature.